Functional coatings for polymer composites - Babik, A.; Hoferek, L.; Janova, D.; Cech, V. (International Conference on Plasma Surface Engineering, 2013)
The development of high-performance polymer composites is tightly bound with the functional surface modification of reinforcements. A new method, based on the principle of the fiber-bundle pull-out test, was used to analyze the interfacial properties between the long fibers in the form of a bundle and the polymer matrix. The pull-out test can be used for a relative comparison of different surface modifications if the bundle geometry is unknown. Glass fibers coated by plasma polymer films of tetravinylsilane were tested to determine the interfacial shear strength as a function of RF power and film thickness that was varied from 50 nm to 10 µm. SEM micrographs of pulled-out (debonded) fiber bundle were used to characterize adhesion at the interlayer/fiber and polymer/interlayer interfaces.